International Resource Tax Policies Beyond Rent Extraction - Lucas Bretschger; Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
We study the incentives of selfish governments to tax tradable primary inputs un- der asymmetric trade. Using an empirically-consistent model of endogenous growth, we obtain explicit links between persistent gaps in productivity growth and the observed tendency of resource-exporting (importing) countries to subsidize (tax) domestic resource use. Assuming uncoordinated maximization of domestic welfare, national governments wish to deviate (i) from inefficient laissez-faire equilibria as well as (ii) from efficient equilibria in which domestic distortions are internalized. The incentive of resource-rich countries to subsidize hinges on slower productivity growth and is disconnected from the typical incentive of importers to tax resource inflows. i.e., rent extraction. The model predictions concerning the impact of resource taxes on relative income shares are supported by empirical evidence.
Keywords: F43; O40; 330; Productivity Growth; Exhaustible Resources; International Trade